Shooting techniques in archery sport based on biomechanics engineering: arm vibration analysis - Siti Nurhidayah, Daud (2013)
This thesis is mainly about the archery sports and focusing on the shooting techniques that finally will be result in accuracy of the shots and performance of the athlete. There are several steps that need to be followed to obtain the correct postural during the archery session. This may influent the result of the arrow release later. The aim of this study was to investigate the relationship between arm vibration during the shooting process with the score and performance of the athlete and to investigate the relationship between the time taken for the athlete to release the arrow with the score and performance of the athlete. Suitable outdoor experiment setup will be recommended inside this paper work. Accelerometer will be used in this experiment. Other equipment involve including DAQ device, camera digital, cable, and target board. Vibration rate data will be collected and analyze by using the DASYLab software. Time taken for the archer to release the arrow also will be recorded to investigate either it will give a significant to the performance of the athletes. From the results, it shows that there are significant relationship between arm vibration and time with the performance of the athletes. Statistical analysis that consists of regression and ANOVA also conducted in this project to show the correlation between the variables involves